Trends for the Development of Wellness Tourism in Bulgaria During Digital Revolution - Dimova, Denitsa (Research Papers, 2022)
Wellness tourism is among the best-developed and promising specialized types of tourism in the world. To reach full utilization and future development of this alternative type of tourism, it is necessary to first collect and coordinate good practices that could be adapted to the current state of wellness tourism in Bulgaria in order to improve its overall state. The international trends and experience indicate as its main direction the digitalization, which is applicable in the entire tourism industry, including wellness. This determines the relevance of the topic related to the need to evaluate the real effect of digitalization on wellness tourism, particularly in Bulgaria. Modern technologies are changing the entire tourist environment, and in Bulgaria, there is a void of current data and information on the correlation between technological progress and wellness tourism. After the analysis of the current digital situation of the wellness destination Bulgaria, recommendations could be made to serve as a basis for preparing a strategic plan for the future development of the sector. Destination Bulgaria needs to strengthen its current position in the tourist wellness market and evaluate the effect of digitalization in the sector and equate it to new trends and requirements that are fundamental for future prosperity. The methodology of the research is based on systematic and holistic approaches, and it covers: analysis and synthesis, induction and deduction, analogy, comparative analysis, statistical and descriptive methods.
Keywords: Wellness tourism; Future development; Conclusions; Tasks; Recommendations; Digitalization; Analysis